2-(4-nitrophenyl)iminomethyl phenol Schiff base metal complexes: Synthesis, spectroscopic characterization, anticancer and antimicrobial studies. Issue 9 (1st August 2022) - Sekhar, E. Vijaya; Rangaswamy, Javarappa; Bhat, Mahesh; Naik, Nagaraja
Abstract: An imine-based molecule, 2-(4-nitrophenyl)iminomethyl phenol Schiff base (NPIMP ) ligand was synthesized by microwave and conventional methods by reaction between 4-nitroaniline (1) and salicyaldehyde (2) . The metal complexes of La(III), Co(II), Ni(II) and Cu(II) (3a-d) with NPIMP were synthesized as potential anticancer and antimicrobial drug candidates. The synthesized ligand and metal complexes were structurally characterized by spectral (NMR, FT-IR, LC-MS and UV-Vis), scanning electron microscopy, elemental analysis, powder X-ray diffraction and thermo gravimetric (TG) data. Spectroscopic studies suggested a distorted octahedral structure for all the complexes. The systems were evaluated for their anticancer and antimicrobial activities. The anticancer activity studies revealed that all the complexes exhibited promising activity against MCF-7 breast and HeLa cell lines. Antimicrobial activity has shown that all the complexes were showed certain degree of activity. As for the antimicrobial activity, La(III) and Co(II) complexes displayed potential antibacterial and antifungal activity against the tested microbes.